2002
DOI: 10.1073/pnas.252522299
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale molecular dynamics simulations of general anesthetic effects on the ion channel in the fully hydrated membrane: The implication of molecular mechanisms of general anesthesia

Abstract: Interactions of volatile anesthetics with the central nervous system are characterized by low yet specific binding affinities. Although neurotransmitter-gated ion channels are considered the primary anesthetic targets, the mechanism of action at the molecular level remains elusive. We consider here the theoretical implications of channel dynamics on anesthetic action in a simplified membranechannel system. Large-scale 2.2-ns all-atom molecular dynamics simulations were performed to study the effects of halotha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

23
149
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(172 citation statements)
references
References 44 publications
23
149
0
Order By: Relevance
“…general anesthetics | drug-protein interaction | voltage-gated sodium channel | nuclear magnetic resonance | molecular dynamics simulation G eneral anesthetics disrupt sensory communications by modulating proteins in the central nervous system (1)(2)(3)(4). For many years, the physiological relevance of a protein class to general anesthesia has been judged based on the protein's sensitivity to anesthetics, particularly the steepness of the in vitro concentration dependence, in comparison with that of the in vivo doseresponses.…”
mentioning
confidence: 99%
“…general anesthetics | drug-protein interaction | voltage-gated sodium channel | nuclear magnetic resonance | molecular dynamics simulation G eneral anesthetics disrupt sensory communications by modulating proteins in the central nervous system (1)(2)(3)(4). For many years, the physiological relevance of a protein class to general anesthesia has been judged based on the protein's sensitivity to anesthetics, particularly the steepness of the in vitro concentration dependence, in comparison with that of the in vivo doseresponses.…”
mentioning
confidence: 99%
“…Cantor (1997) suggested a mechanism linking the membrane lateral-pressure profile to the action of membrane proteins. The importance of nonspecific interactions mediated by the amino acid residues in the lipid-water-protein interface was highlighted in a recent molecular-dynamics simulation of the effects of an anesthetic on gramicidin channels in membranes (Tang and Xu, 2002).The nongenomic effects of steroids, such as anesthesia, require higher steroid concentrations to manifest themselves than those mediated by the nuclear steroid receptors (Duval et al, 1983). Although these nongenomic effects are welldocumented, their mechanisms are still in dispute, and a number of molecular-level events could be involved.…”
mentioning
confidence: 99%
“…Cantor (1997) suggested a mechanism linking the membrane lateral-pressure profile to the action of membrane proteins. The importance of nonspecific interactions mediated by the amino acid residues in the lipid-water-protein interface was highlighted in a recent molecular-dynamics simulation of the effects of an anesthetic on gramicidin channels in membranes (Tang and Xu, 2002).…”
mentioning
confidence: 99%
“…Halogenated gases modify membrane fluidity and/or membrane proteins (Tang and Xu, 2002;Hauet et al, 2003). ENaCs respond to changes in lipid membrane properties induced by temperature (Chraibi and Horisberger, 2002) or by lipid-perturbing agents (Awayda et al, 2004) by modifying the degree of their selfinhibition.…”
Section: Mechanisms Of Action Of Halothane On Ion Channelsmentioning
confidence: 99%
“…Halothane is known to influence membrane lipid bilayer fluidity through reorientation of the lipid tails (Hauet et al, 2003) and has been recently shown to increase the segmental order of the lipids close to the membrane surface in membrane simulation models (Pickholz et al, 2005). Halothane, which distributes at the liquid-aqueous interface of cell membranes, can partition into amphiphilic membrane domains, thereby potentially changing the behavior of transport proteins (Tang and Xu, 2002). Because ENaC activity decreases with decreasing lipid ordering (Awayda et al, 2004) and is stimulated by cooling, which increases lipid order (Chraibi and Horisberger, 2002), halogenated gases may, at least partly, change ENaC protein conformation through an increase in segmental order leading to an increase ENaC activity.…”
Section: Mechanism Of Enac Activation By Halothanementioning
confidence: 99%